Coordinated Control of SVC and PSS for Transient Stability Enhancement of Multi-Machine Power System - Lin Xu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The coordinated control for SVC and generic/multi-band PSS for power swing damping is presented for the multimachine power system. The background and the mathematical models of the generic PSS, the multi-band PSS and the SVC are presented. The V-I characteristics as well as the dynamic properties of the static var compensator (SVC) are presented. The multi-machine power system is simulated using MATLAB and the effect of PSS and SVC on dynamic response of the system under single-phase fault and three-phase fault are simulated. The simulation results reveal that the coordinated control of the SVC and the generic/multi-band PSS is an effective solution to damp low frequency oscillation for multimachine power system and enhance global stability of the large inter-connected power system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1756